The Combined Effect of Nanoclay and alpha-tocopherol on Mechanical and Physical Properties of Polyethylene Active Packaging - Mirkhavar, Zahra; Ahmadi, Shervin; Farhoodi, Mehdi; Mohammadi, Abdorreza; Mohammadifar, Mohammad Amin (Asian Journal of Biological and Life Sciences, 2018)
A novel active nanocomposite packaging based on low-density polyethylene (LDPE), Cloisite® 15 A (C15A), and α -tocopherol (α-TOC) was prepared. The effects of C15A (0-4 wt. %) and α-TOC (1-3 wt. %) on optical, mechanical and barrier properties of polyethylene were analyzed using the Response Surface Methodology (RSM). Regression models were developed for mechanical characteristics (tensile strength and elongation at break), water vapor permeability (WVP) and optical properties (L*, a*, b*, OP) as a function of α-TOC and C15A concentrations. For all cases, the quadratic terms of the model were significant (P< 0.05). In order to maximize TS and EL and minimize WVP, the desirability function (DF) was used to determine the regression model equations. The optimized factors were found to be 2.93 wt. % α-TOC and 4 wt.% Cloisite®15A for a maximal desirability of 0.903.
Keywords: Active packaging; Cloisite®15A; Nanocomposite; RSM; α-tocopherol